Tooth Contact Analysis of Profile-Shifted Face Gear with Double-Crowned Pinion - Li Wei; Wang Dan; Fu Xuezhong (Jixie chuandong)
The coordinate systems for the processing and driving of the profile-shifted spur pinion with double-crowned and the profile-shifted face gear are established,the tooth surface equations of the profile-shifted pinion and the profile-shifted face gear are deduced,while the tooth surface is simulated for visualization.The modified tooth surface is precisely represented by a sum of two vector functions that determine the theoretical tooth surface and deviation surface.The tooth contact analysis is conducted for the alignment errors of the driving system,and the tooth contact path and the transmission error are computed.The results show that it enables the transmission error to form second order parabolic function with opening down through this method,the sensitivity of contact patch for the alignment errors is reduced,and the meshing performance of profile-shifted face gear drive is improved.